An international instant-messaging journal club: a modern, fun and global approach to a traditional teaching tool. (January 2020) - Peponis, Christos; Khaliq, Mehnoor; Ismail Ali, Abdirashid; Bose, Deepa; Wicks, Laurence; Tessema, Geletaw
The aim of this study was to introduce a modern, engaging and easily accessible approach to medical education. A virtual journal club (VJC) was established for the orthopaedic trainees of Ethiopia using instant messaging via Viber. Group discussions included research articles, case reports and radiographs. In addition, senior participants posed quiz questions, with a leaderboard for best performance. Finally, a satisfaction survey was conducted using Google Forms. We have accumulated data from the first five months of educational activity with 73 participants. Seven articles were analysed and debated, covering a broad range of orthopaedic topics, with 56 messages per article on average and 60 quiz questions overall. Our survey received 20 responses, where 95% perceived the VJC as superior to the traditional journal club. Instant messaging is recommended as an educational tool, utilised as an effective VJC. It provides continuous interactive distance learning, without the restrictions of traditional methods.